2008
DOI: 10.1007/s10549-008-9982-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures suggest a major role for stromal cells in development of invasive breast cancer

Abstract: Based on identified molecular cross-talk between the two contiguous cell populations, a mechanistic model that spurs invasion is proposed, that shows breast cancer invasion proceeds through the acquisition of a motile phenotype in tumor epithelial cells and a reactive phenotype in cancer associated fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 92 publications
5
180
1
1
Order By: Relevance
“…separated by laser capture microdissection (from n = 28 human breast cancer patients). 42 As shown in Table 1, important functional components involved in both mitochondrial biogenesis and/or mitochondrial translation were all transcriptionally upregulated in human breast cancer epithelial cells and, hence, downregulated in adjacent stromal cells. Only gene transcripts upregulated by > 1.5-fold are shown.…”
Section: Resultsmentioning
confidence: 99%
“…separated by laser capture microdissection (from n = 28 human breast cancer patients). 42 As shown in Table 1, important functional components involved in both mitochondrial biogenesis and/or mitochondrial translation were all transcriptionally upregulated in human breast cancer epithelial cells and, hence, downregulated in adjacent stromal cells. Only gene transcripts upregulated by > 1.5-fold are shown.…”
Section: Resultsmentioning
confidence: 99%
“…to determine if PGC1a/NrF1 activity is upregulated in human breast cancers, we performed a bioinformatics analysis. Briefly, we re-interrogated a set of n = 28 human breast cancer patient samples 83 in which the tumor stroma and epithelial cancer cells were separated by laser-capture microdissection. the transcriptional profiles of these two cellular compartments (epithelia vs. stroma) were used to generate a list of genes that were upregulated in epithelial cancer cells, relative to adjacent stromal tissue (2,901 transcripts upregulated > 2-fold; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Here, to determine if PGC1a and NRF1 (nuclear respiratory factor 1) activity is upregulated in human breast cancers, we performed a bioinformatics analysis using existing published data sets. For this purpose, we re-interrogated a set of n = 28 human breast cancer patient samples 83 in which the tumor stroma and epithelial cancer cells were physically separated by laser recent study directly showed that targeted deletion of PGC1a in mice prevents carcinogen-induced epithelial tumorigenesis in the liver and the colon. 78 Conversely, overexpression of PGC1a in cancer cells dramatically increases tumor growth in murine animal models.…”
Section: Visualizing Two-compartment Tumor Metabolism: Hyperactivatiomentioning
confidence: 99%
“…Heparanase and MMP-9 apprear to be involved in this regulation. These results broaden the view of cancer, which is at present focused on oncogenes and tumor suppressor genes, to include the viewpoint that the tumoral microenvironment co-evolves and interacts in a dynamic and reciprocal way with mutated epithelium (24,25). The experimental model presented is in keeping with the characteristics of the physiological environment of breast epithelial cells in terms of both the soluble and insoluble factors present and the stromal structure per se.…”
Section: Discussionmentioning
confidence: 78%